Learning to replace a human: A virtual performing agent - McCormick, John; Hutchison, Steph; Nash, Adam; Vincs, Kim; Nahavandi, Saeid; Creighton, Douglas (International Journal of Virtual Reality, 2015)
In this paper we describe two artworks, Recognition, an outdoor interactive installation and Instrumental a live dance performance. In both works a performing agent has learnt sequences of movement from a dancer and uses these to stand in for a human performer. The agent uses an Artificial Neural Network to learn to dance from the human dancer and can perform in the human's stead. In Recognition the agent's movement is used when there are no humans present in order to keep continuity of the installation. In Instrumental the agent becomes a performing partner of a live human dancer, able to recognize the dancers movement and synthesize movement sequences based on the human dancer's movements.